High incidence of pulmonary tuberculosis in children admitted with severe pneumonia in Uganda - Nantongo Josephine M (BMC Pediatrics, 2013)
Abstract Background A high prevalence of tuberculosis (TB) in children presenting with severe pneumonia has previously been reported in South Africa. However, little is known about TB among children with pneumonia in Uganda and other resource limited countries. Moreover, TB is associated with high morbidity and mortality among such children. We conducted this study to establish the burden of pulmonary TB in children admitted with severe pneumonia in our setting. Methods A cross-sectional study was conducted at Mulago, a National Referral and teaching hospital in Uganda. Hospitalised children 2 months to 12 years of age with severe pneumonia based on WHO case definition were enrolledfrom February to June 2011. Children with a previous TB diagnosis or receiving anti-TB treatment were excluded. Each child was screened for TB using Tuberculin skin test, Chest X-ray, induced sputum samples and blood culture for mycobacterium. Sputum smears were examined using fluorescent microscopy, and cultured on both Lowenstein Jensen media (LJ) and Mycobacterial Growth Indicator Tubes (MGIT). Results Of the 270 children with severe pneumonia who were recruited over a 5-month period in 2011, the incidence ratio of pulmonary TB in children admitted with severe pneumonia was 18.9% (95% CI 14.6 – 23.9). The proportion of culture confirmed PTB was 6.3% (95% CI 3.8 – 9.7). Age group under 1 year and 1 to 5 years (OR 2.8 (95% CI 1.7 – 7.4) and OR 2.4 (95% CI 1.05 – 5.9) respectively) were more likely to be associated with pulmonary TB compared to those children over 5 years of age. A history of TB smear positive contact was associated with pulmonary TB (OR 3.0 (95% CI 1.3–6.5). Conclusions We found a high burden of pulmonary TB in children admitted with severe pneumonia. These data highlight the need for TB screening in children admitted with severe pneumonia so as to improve TB case finding and child survival.